2024
DOI: 10.1186/s12902-024-01554-z
|View full text |Cite
|
Sign up to set email alerts
|

Association between weight-adjusted waist index and non-alcoholic fatty liver disease: a population-based study

Changhui Yu,
Shiming He,
Maobin Kuang
et al.

Abstract: Background Obesity is the most important driver of non-alcoholic fatty liver disease (NAFLD); nevertheless, the relationship of weight-adjusted waist index (WWI), a new obesity index, with NAFLD is unclear. Methods This retrospective study used data from the NAGALA project from 1994 to 2016. WWI values were calculated using waist circumference (WC) and weight measurements of the participants. Three stepwise adjusted logistic regression models were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…However, the validity of these indicators needs to be confirmed by more extensive clinical studies. In recent years, it has been found that WWI is a superior predictor of non-alcoholic fatty liver disease [ 33 ], low cognitive performance [ 27 ], hyperuricemia [ 28 ], diabetic kidney disease [ 42 ], kidney stones [ 30 ], stress urinary incontinence [ 31 ], and depressive symptoms [ 43 ]. WWI has excellent potential as an anthropometric indicator because of its easy computation and strong ability to forecast disease onset [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the validity of these indicators needs to be confirmed by more extensive clinical studies. In recent years, it has been found that WWI is a superior predictor of non-alcoholic fatty liver disease [ 33 ], low cognitive performance [ 27 ], hyperuricemia [ 28 ], diabetic kidney disease [ 42 ], kidney stones [ 30 ], stress urinary incontinence [ 31 ], and depressive symptoms [ 43 ]. WWI has excellent potential as an anthropometric indicator because of its easy computation and strong ability to forecast disease onset [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The weight-adjusted-waist index (WWI) represents a novel metric for obesity assessment, demonstrating enhanced precision in quantifying lean muscle and adipose tissue mass when juxtaposed with traditional measures such as BMI and waist circumference (WC) [ 26 , 27 ]. The literature suggests that WWI is associated with a variety of conditions, including fatty liver, cognitive function, hyperuricemia, diabetes mellitus, kidney stones, dyslipidemia, and urinary incontinence [ 28 , 27 , 29 33 ]. It may serve as a more accurate predictor of risk.…”
Section: Introductionmentioning
confidence: 99%